GAMBARAN GAYA HIDUP PASIEN GAGAL GINJAL KRONIK DI RUANG HEMODIALISA RSUD Dr. HARJONO PONOROGO - Nurmanita, Nurmanita; Rosita, Ani; Nurjayanti, Dwi (WARTA BHAKTI HUSADA MULIA : Jurnal Kesehatan, 2020)
Based on estimates by the world Health Organization (WHO), globally more than 500 million people experience chronic kidney disease. About 1.5 million people have to hope live on hemodialysis. Especially in the hemodialisa room at Dr. Harjono Ponorogo Hospital. The frequency of hemodialysis everyday is 3 times and every time hemodialisa have 20 patients everyday. Type of this research is descriptive. Data collection teqniques with observation, interview. Koesioner and dokumentation. The data samples in this study were some chronic kidney disease patients on terapy in the hemodilysis room at Dr. Harjono Ponorogo Hospital in may 2019. The samples tecniques was done using samples accidental. The independent variables in this study were lifestyle (eat habits, body activity, and smoke behavior). The resulth of research found that in cronic kidney disease patients hemodialisa room at Dr. Harjono Ponorogo Hospital most had well eat habits, that is 37 respondents (95,5%) of 40 respondentd. Slight Body activity that is 21 respondent (52,5%) of 40 respondents. Smoke behavior patients 37 respondents (92,5%) of 40 respondents did not smoke. Life style of patients 39 respindents (97,5%) of 40 respondents had a good lifestyle. Suggestion it is expected that chronic kidney disease should change their lifestyle better to improve the health quality of their own patients.